Marshall Test Comparison of Asphalt Mix PG 70 and Asphalt Pen 60/70 Based on Bina Marga General Specification - Putri, Mutiara Mentari; Gusty, Sri; Indrayani, Poppy (Universitas Ibn Khaldun Bogor, 2025)
Marshall Test Mix Asphalt PG 70 and Asphalt Pen 60/70. Marshall aims to determine the characteristic of the dough in the test object. In this case to know the values of durability (stability), melting (flow), & marshall Qouintient. The Marshall tool is a pressure sensor which is equipped with a proving ring with a capacity of 22.5 KN or 5000 IBS. The proving ring is equipped with a measuring watch which is useful for measuring the stability of the dough. Apart from that, there is still a flow meter to measure plastic melting, because the basic principle of the Marshall method is inspection of stability & melting (flow), and analysis of density & pores based on the dough that is formed. The dough design of the Marshall method was discovered by Bruce Marshall, & has been standardized by ASTM or AASHTO through several modifications, namely ASTM D 1559-76, or 27 AASHTO T T-245-90. The standard Marshall Test object is a cylinder with a diameter of 4 inches (10,16 cm) and a heigt of 2,5 inches (6,35 cm).